Pautas de Crianza Asociadas a Comportamientos Violentos en los Estudiantes del Grado 6° de una Institución Educativa del Municipio de Maicao La Guajira (2021)
The way the human being behaves or develops in his daily life is nourished by the experiences that from the first years of life acquire as a person the which develops the perspective or vision of seeing life, the referents are the parents or adults who are in charge of their upbringing are that guide from which the first behavior or attitudes you have is based on them. From the beginning it is necessary to provide tools correct for their cognitive and emotional development adequately